Benefit of continuous kidney replacement therapy for managing tumor lysis syndrome in children with hematologic malignancies - Anderson, Ashlea; Shoulders, Laurie; James, Vinson; Ashcraft, Emily; Cheng, Cheng; Ribeiro, Raul; Elbahlawan, Lama (Frontiers in Oncology, 2023)
Introduction: Tumor lysis syndrome (TLS) is often diagnosed in children with hematological malignancies and can be life threatening due to metabolic disturbances. Continuous renal replacement therapy (CKRT) can reverse these disturbances relatively quickly when conventional medical management fails. Our objective was to investigate the benefit of CKRT in the management of TLS in children admitted to the intensive care unit with hematologic malignancies. In addition, we sought to assess risk factors for acute kidney injury (AKI) in the setting of TLS.Retrospective review of all children admitted to the intensive care unit with TLS who